Endocannabinoids Interact With the Dopaminergic System to Increase Sexual Motivation: Lessons From the Sexual Satiety Phenomenon - Canseco-Alba, Ana; Rodríguez-Manzo, Gabriela (Frontiers in Behavioral Neuroscience, 2019)
In male rats, copulation to satiety induces a long-lasting sexual inhibitory state, considered to rely on a decreased sexual motivation. Dopaminergic transmission at the mesolimbic system plays a central role in the regulation of male sexual motivation. Endocannabinoids modulate the activity of the mesolimbic system and both dopamine and cannabinoid receptor activation reverse the sexual inhibition that characterizes sexually satiated rats. The endocannabinoid anandamide reverses sexual satiety when systemically administered or infused into the ventral tegmental area, the region where the activity of mesolimbic dopaminergic neurons is regulated. Thus, it could be thought that sexual motivation is diminished during the long-lasting sexual inhibition of sexually satiated rats and that endocannabinoids reverse that inhibition through the modulation of the dopaminergic system. To test this hypothesis, we assessed the motivational state of sexually satiated male rats and determined if 2-AG, the most abundant endocannabinoid and a full cannabinoid receptor agonist, also reversed the sexual inhibitory state. To establish the possible interaction between 2-AG and anandamide with the dopaminergic system for the reversal of sexual satiety, we analyzed the effects of the co-administration of each endocannabinoid and dopamine receptor agonists or antagonists. Results showed that 24-h after copulation to satiety, when the sexual inhibition is well established, the males’ sexual motivation is diminished as measured in the sexual incentive motivation test. 2-AG, similarly to anandamide, reverses sexual satiety through the activation of CB1 receptors and both endocannabinoids interact with the dopaminergic system to reverse the sexual inhibitory state. 2-AG effects are mediated by the modulation of the D2-like dopamine receptor family, whereas anandamide’s effects are clearly mediated by the modulation of the D1-like dopamine receptor family and the activation of D2-like dopamine receptors. Present results evidence that a reduced sexual motivation underlies the sexual inhibitory state of sexually satiated rats and support the notion that endocannabinoids reverse sexual satiety by modulating dopaminergic transmission, presumably at the mesolimbic system. Anandamide and 2-AG have a different interaction with D1-like and D2-like dopamine receptor families. Altogether present data endorse the association of the endocannabinoid system with the regulation of the motivational tone at the mesolimbic system.